Sustainable palm oil processing : Towards zero discharge of POME treatment - Li Goajie (Malaysian Palm Oil Board, 2015)
`Palm oil industry in Malaysia has grown rapidly over the years and contributes towards the country's foreign exchange earnings and the increased standard living among Malaysians. Malaysia contributes 41% of world's palm oil production and 47% of world's export. Standing in line with other palm oil producers, Malaysia is placed second in production and the main exporter in oil palm industry. Palm oil mill effluent (POME) is generated in the extraction process, which is during the procedures of sterilization,stripping, digestion, pressing, classification, purification and vacuum drying. POME consists of water soluble components of palm fruits as well as suspended materials like palm fibre and oil. Despite its biodegradability, POME cannot be discharged without first being treated because POME is acidic and has a very high biochemical oxygen demand (BOD). Therefore, POME is being characterized as high pollutant. In palm oil milling, the treatment of POME is very critical to conserve the environment due to the emissions of biogas from POME and the concern on quality of the final discharge to the watercourse. Currently, conventional ponding process has been a widely acceptable method to reduce the biological and chemical constituents of POME. This method, even though simple and reliable, generates large amounts of sludge, longer retention time and consumption of large land areas. It is thus justified that many studies have been conducted to develop alternative methods for POME treatment with possibilities of resource recovery by smaller and higher efficiency treatment system. Throughout the entire development of oil palm industry in Malaysia, both upstream and downstream, the oil palm and its products have always been linked with the environment. It is this sensitivity to the environment that sees the initiation of zero-discharge concept, which mainly routed in "Pretreatment - Biological processes - Membrane separation". The transformation of conventional wastewater treatment system, that is open pond system, to a more advanced and efficient AnaEG TM and BioAX TM, obviously provide new opportunities and challenges in this industrial sector. The proposed "zero discharge" treatment process is developed based on clean development mechanist (CDM) and sustainable development strategy, which is not only for environmental protection but also exploring the potential market of CDM in Malaysia's palm oil industry.